Desain Kurikulum Darurat Saat Pandemi Covid-19 Mata Pelajaran Akidah Akhlak di MTs Negeri 5 Kulon Progo - Ismunandar Ismunandar (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
The purpose of this study was to describe the emergency curriculum design during the Covid-19 pandemic for Akidah Akhlak subjects at MTs Negeri 5 Kulon Progo. The research method used is descriptive research using a qualitative approach. Data collection techniques with interviews and observations. The data analysis technique used is phenomenological analysis, which is a technique for drawing conclusions based on the data obtained and in accordance with the research objectives. The results of this study are the emergency curriculum design during the Covid-19 pandemic, the eyes of Akidah Morals at MTs N 5 Kulon Progo were compiled due to limitations in the implementation of learning for students both in terms of time and conditions because students must continue to study at home. So it is not possible to complete all chapters in the subject matter of Akidah Akhlak. This will continue as long as the pandemic is not over.